Loss, Mourning, and the Developmental Process: Thoughts on Jane. Issue 1 (31st December 2023) - McGehee, Rex
ABSTRACT: This is the discussion of the analysis of an adolescent who had traumatically lost her mother as a school-age child. Using the case material presented by Cheryl Collins, the discussion will present the unconscious developmental dilemma posed by loss. Faced with the pain of loss, the process of development may deviate into a painful world of melancholia, nostalgia, and the repeated experiencing of the disappointing and painful object relationships of a closed system. Analysis offers the patient the opportunity to begin the grieving process, introduce new objects, and further the adaptive developmental process of increasingly organized complexity.